Assessment of the synergistic pressures on zooplankton in the Euphrates River - Sadiq Sahib Mohammed; Mahmood Basil Mahmood (Zien Journals, 2022)
The current study clarified the effect of multiple pressures The current study showed the effect of multiple pressures resulting from the Nasiriyah power plant (NPP) such as thermal pollution, total petroleum hydrocarbons, and predation on the composition and density of the zooplankton community in the Euphrates River. Four stations were selected on the course of the river. Several physical and chemical variables with a direct effect on the presence of zooplankton in river water such as air and water temperature, salinity, and electrical conductivity were selected. A search and survey have been conducted for the predatory fish of the zooplankton in the river waters.
Keywords: selected; search; conducted; zooplankton